ON ACCOUNT DELETION IN MARKETPLACE: A JUSTICE PERSPECTIVE - Anis W. Hermawan (Scientia Integritas Utama, 2022)
The existence of Article 59 paragraph (4) of Government Regulation Number 80 of 2019 and Article 26 paragraph (3)-paragraph (5) of Law Number 19 of 2016 has the potential to cause injustice for several other government bodies, such as tax authorities, customs and excise authorities, and local governments. This problem can be answered based on normative legal methods. Based on analysis and discussion, two conclusions were produced. First, prevailing laws governing the deletion of data and/or accounts at customers’ request to the marketplace are contrary to lex-specialists of several other government agencies. Second, legal updates that have the concept of fairness are adequate in reformulating the deletion of data and/or customer accounts to the marketplace. It is recommended that there be rules on certificates from certain government agencies, for example, those related to efforts to re-cover state and regional financial losses, against customers who request the deletion of their data or accounts to a marketplace. In addition, it is necessary to regulate legal liability for marketplace containers that delete customer data and/or accounts without being proven by clarifica-tion letters or certificates from certain government agencies, such as implementing institutions of Law No. 8 of 1997, Law No. 17 of 2006, Law No. 1 of 2022, and KUP Law.